A high-process-tolerance silicon nitride whisker reinforced nickel-based alloy composite material and additive manufacturing method
Patent Information
- Application Number
- CN202611477271.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-22
- Publication Date
- 2026-10-27
AI Technical Summary
IN718合金在SLM成形过程中由于热应力集中和元素偏析,易产生微裂纹,降低成形件的致密度和力学性能
1、高工艺宽容度--稳定的力学性能输出:现有SLM成形IN718合金对工艺参数极为敏感,工艺窗口窄,参数波动会导致成形质量显著下降。本发明通过Si3N4晶须的均匀混合与多重增韧机制,使复合材料在激光功率250-350W、扫描速度700-1000mm/s、扫描间距80-100μm的较宽范围内均能获得致密无裂纹的成形件,且抗拉强度均稳定在900-1034MPa范围内(经17组Box-Behnken设计实验验证,各工艺参数对拉伸性能的影响不显著)。这一特性大幅降低了对工艺控制的要求,显著提高了生产的稳定性和良品率,具有重要的工程应用价值。
Smart Images

Figure CN122979707A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of additive manufacturing technology, specifically to a silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance and an additive manufacturing method thereof. Background Technology
[0002] IN718 (Inconel 718) nickel-based superalloys are widely used in high-end manufacturing fields such as aerospace and energy chemicals due to their excellent high-temperature strength, oxidation resistance, and corrosion resistance. Selective laser melting (SLM), as an advanced additive manufacturing technology, can achieve the one-piece forming of complex structural metal parts, and has significant advantages in the rapid manufacturing of IN718 alloy components.
[0003] However, SLM forming of IN718 alloy presents the following technical problems: First, the process window is narrow. The SLM forming quality of IN718 alloy is extremely sensitive to process parameters such as laser power, scanning speed, and scanning spacing. Improper parameter settings can easily lead to defects such as porosity, cracks, spheroidization, and warping, severely limiting the density and mechanical properties of the formed parts. In actual production, to obtain stable forming quality, a significant amount of time and cost is usually required for fine optimization of process parameters. Currently, there is an urgent need to develop an IN718 composite material and its forming method that is insensitive to process parameters and has high process tolerance.
[0004] Second, it has high crack sensitivity. During the SLM forming process, IN718 alloy is prone to microcracks due to thermal stress concentration and element segregation, which reduces the density and mechanical properties of the formed parts.
[0005] Third, subsequent heat treatment is required. Currently, SLM-formed IN718 alloys typically require standard heat treatments such as solution treatment and aging to obtain high mechanical properties, which increases process complexity and manufacturing costs.
[0006] Adding ceramic reinforcing phases to nickel-based alloys is one of the effective ways to improve the above-mentioned problems. Whiskers, as a one-dimensional ceramic reinforcing material, have the characteristics of high aspect ratio, high strength and good thermal stability, and can play a role in multiple reinforcement and toughening mechanisms in composite materials, such as bridging cracks, deflecting cracks, and pull-out toughening. Si3N4 whiskers (length 10-40μm, diameter 3-5μm), as a typical ceramic whisker reinforcement, have high melting point, high hardness, good thermal stability and chemical stability, and are an ideal reinforcing phase for metal matrix composites.
[0007] However, micron-sized whiskers suffer from severe agglomeration and uneven dispersion during powder mixing. Traditional ball milling methods disrupt the aspect ratio of the whiskers and make it difficult to achieve uniform distribution of whiskers in metal powders. Acoustic resonance mixing technology, as a novel powder mixing method, utilizes the superposition of resonant energy to create a chaotic motion state in the material within the reaction chamber. This allows for the rapid and uniform mixing of the reinforcing phase in metal powders while maximizing the preservation of the original metal powder's sphericity and flowability.
[0008] Currently, there are no reports on the preparation of composite materials with high process tolerance by uniformly doping Si3N4 whiskers into IN718 alloy powder using acoustic resonance mixing technology and combining it with SLM technology.
[0009] Therefore, developing a Si3N4 whisker-reinforced IN718 composite material based on acoustic resonance mixing and its SLM additive manufacturing method, which enables the composite material to stably obtain excellent mechanical properties over a wide range of process parameters, has significant industrial application value. Summary of the Invention
[0010] The purpose of this invention is to provide a silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance and an additive manufacturing method. By using acoustic resonance mixing technology to achieve uniform mixing of Si3N4 whiskers in IN718 alloy powder, the composite material can obtain dense, crack-free, and mechanically excellent formed parts within a wide range of SLM process parameters. This solves the problems of narrow process window, easy cracking, and need for subsequent heat treatment in existing SLM forming of IN718 alloy.
[0011] The technical solution of the present invention to solve the above-mentioned technical problems is as follows: a silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance is provided. The composite material is composed of a nickel-based alloy matrix and a silicon nitride whisker reinforcing phase. The silicon nitride whiskers are uniformly distributed in the nickel-based alloy matrix. The composite material is dense and crack-free. When the composite material is used for selective laser melting forming, it has high process tolerance.
[0012] Furthermore, when the composite material is used for selective laser melting forming, under the process parameters of laser power 250-350W, scanning speed 700-1000mm / s, and scanning spacing 80-100μm, the tensile strength of the obtained composite material is 900-1034Mpa.
[0013] Furthermore, the silicon nitride whiskers have a length of 10-40 μm, a diameter of 3-5 μm, and an aspect ratio of 2-13.
[0014] Furthermore, the nickel-based alloy matrix is IN718 nickel-based alloy powder, and the particle size of IN718 nickel-based alloy powder is 15-65μm.
[0015] Furthermore, the amount of silicon nitride whiskers added is 5% of the total mass of the composite material.
[0016] The preparation method of the above-mentioned silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance includes the following steps: A nickel-based alloy matrix and silicon nitride whiskers are subjected to acoustic resonance mixing under a protective atmosphere to obtain a silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance.
[0017] Furthermore, during the acoustic resonance mixing process, the resonance frequency is 50-60Hz, the acceleration is 20-40g, and the mixing time is 3-10min.
[0018] Furthermore, during the acoustic resonance mixing process, the resonance frequency was 55Hz, the acceleration was 30g, and the mixing time was 5min.
[0019] The present invention also provides an additive manufacturing method, comprising the following steps: The aforementioned silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance was formed by selective laser melting. During selective laser melting, the laser power was 250-350W, the scanning speed was 700-1000mm / s, the scanning spacing was 80-100μm, the powder thickness was 40μm, and the scanning strategy was 67° stripe rotation scanning.
[0020] Furthermore, the material is formed by selective laser melting under the protection of high-purity argon gas.
[0021] In this invention, acoustic resonance mixing technology is used to achieve uniform mixing of Si3N4 whiskers in IN718 powder. The principle is as follows: the acoustic resonance mixing device drives the mixing tank to generate high-frequency, low-amplitude vibrations at a resonant frequency (approximately 55Hz), causing the powder material inside the tank to form continuous chaotic convection motion in three-dimensional space—the material is constantly thrown up, tumbled, and redistributed within the tank, forming a composite flow field of "overall motion + local convection." This flow field has the characteristics of uniform energy distribution and no dead zones, enabling uniform mixing of powder particles of different sizes and densities at both macroscopic and microscopic scales.
[0022] Unlike traditional ball milling, which relies on mechanical impact and shearing force, this method works by causing the entire mixing tank to vibrate at a resonant frequency. Energy is directly transferred to all materials inside the tank. The energy input method of acoustic resonance mixing is gentler than the energy transfer through the impact of grinding media (such as grinding balls). While achieving thorough mixing of powders, it does not cause mechanical damage such as breakage or bending of whiskers, thus preserving the high aspect ratio of the whiskers.
[0023] In the subsequent SLM forming process, the Si3N4 whiskers uniformly distributed in the IN718 matrix mainly play the following toughening mechanisms: (1) Crack bridging - when microcracks are generated in the matrix, the whiskers that cross the crack surface can bridge the two sides of the crack and bear part of the load; (2) Crack deflection - the presence of whiskers causes the crack propagation path to deflect, increasing the length of the crack propagation path and consuming more fracture energy; (3) Whisker pull-out - when the crack propagates to the whisker / matrix interface, the whisker needs to overcome the interface friction force to be pulled out from the matrix, which consumes a lot of energy.
[0024] The synergistic effect of the above-mentioned multiple toughening mechanisms enables the composite material to have good tolerance to fluctuations in process parameters such as laser power, scanning speed, and scanning spacing during SLM forming. Even if a parameter deviates from the optimal value within a certain range, the toughening mechanism of whiskers can still effectively suppress crack initiation and propagation, thereby ensuring that the density and mechanical properties of the formed part remain stable.
[0025] The present invention has the following beneficial effects: 1. High Process Tolerance – Stable Mechanical Property Output: Existing SLM forming of IN718 alloy is extremely sensitive to process parameters, with a narrow process window; parameter fluctuations lead to a significant decrease in forming quality. This invention, through the uniform mixing of Si3N4 whiskers and multiple toughening mechanisms, enables the composite material to obtain dense, crack-free formed parts within a wide range of laser power (250-350W), scanning speed (700-1000mm / s), and scanning spacing (80-100μm), with tensile strength consistently remaining within the range of 900-1034MPa (verified by 17 sets of Box-Behnken design experiments, showing that the influence of each process parameter on tensile properties is insignificant). This characteristic significantly reduces the requirements for process control, substantially improves production stability and yield, and has significant engineering application value.
[0026] 2. Acoustic Resonance Mixing + Uniform Dispersion of Micron-sized Whiskers: This invention employs acoustic resonance mixing technology (55Hz, 30g, 5min) to achieve uniform mixing of micron-sized whiskers (10-40μm length, 3-5μm diameter) in IN718 powder while maintaining whisker integrity. This avoids the damage to whisker aspect ratio and agglomeration problems caused by traditional ball milling mixing, thus maximizing the whisker reinforcement effect.
[0027] 3. Dense and crack-free molded parts: By optimizing the SLM process parameters, dense and crack-free composite material molded parts were obtained, overcoming the technical problem of easy cracking in IN718 alloy SLM forming.
[0028] 4. High strength without heat treatment: Existing SLM forming of IN718 alloy typically requires solution treatment and aging heat treatment to achieve high strength. This invention utilizes multiple reinforcement and toughening mechanisms, including bridging cracks, deflection cracks, and pull-out toughening of Si3N4 whiskers, to enable the formed part to have a tensile strength of 900-1034MPa without standard heat treatment, eliminating the need for subsequent heat treatment processes and reducing manufacturing costs and time to a certain extent.
[0029] 5. Simple and efficient process: The acoustic resonance mixing process is short (5 minutes) and efficient. SLM forming can obtain high-performance molded parts without subsequent heat treatment. The overall process is short and suitable for industrial production. Attached Figure Description
[0030] Figure 1 The image shows a scanning electron microscope (SEM) image of the original IN718 alloy powder in Example 1. Figure 2 Here is a scanning electron microscope (SEM) image of Si3N4 whiskers in Example 1; Figure 3 This is a SEM image of the composite powder after acoustic resonance mixing in Example 1; Figure 4 The tensile stress-strain curves of each composite material molded part are shown. Figure 5 A 3D surface plotting the tensile strength Rm for a fully quadratic model. Detailed Implementation
[0031] The present invention will be further illustrated below with reference to specific embodiments, but the embodiments do not limit the present invention in any way. Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in this technical field.
[0032] Example 1:
[0033] A silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance is prepared by the following steps: (1) Raw material preparation IN718 nickel-based alloy spherical powder was selected, with a particle size range of 15-65μm and a purity ≥99.5%. Figure 1 Si3N4 whiskers were selected, with a length of 10-40 μm and a diameter of 3-5 μm. Figure 2 The Si3N4 whisker content is 5% of the total mass of the composite powder.
[0034] (2) Acoustic resonance mixing IN718 alloy powder and Si3N4 whiskers were added to an acoustic resonance mixing apparatus, which was then evacuated and filled with argon gas for protection. The acoustic resonance mixing apparatus was started for mixing, with the following process parameters: resonance frequency 55Hz, acceleration 30g, and mixing time 5min. SEM images of the mixed composite powder were obtained. Figure 3 The results showed that Si3N4 whiskers were uniformly distributed in IN718 alloy powder, with no obvious agglomeration.
[0035] (3) SLM forming The mixed composite powder is loaded into the powder cylinder of the SLM equipment and subjected to selective laser melting and shaping under the protection of high-purity argon gas. The SLM process parameters are as follows: Laser power: 250W; Scanning speed: 700 mm / s; Scanning interval: 90m; Powder layer thickness: 40m; Scanning strategy: 67° stripe rotation scan.
[0036] (4) Mechanical property testing Room temperature tensile tests were conducted on untreated SLM molded samples according to GB / T 228.1 standard. The results showed that the tensile strength of the composite material was in the range of 900-1034 MPa. Figure 4 ).
[0037] The process parameter optimization experiment was conducted according to the preparation method in Example 1 to verify the high process tolerance. To verify the high process tolerance of the composite material of the present invention, a three-factor, three-level Box-Behnken design method was used to prepare a total of 17 groups of samples (including the center point repeated experiment). The variables and level settings are shown in Table 1, and the specific parameters are shown in Table 2. In Table 2, each experimental group number corresponds to each example, "0" represents the center level, and "-1" and "1" represent the low level and high level, respectively.
[0038] Table 1. Variables and level settings for the three-factor, three-level Box-Behnken design method.
[0039] Table 2. Specific parameter combinations for 17 experimental groups
[0040] Fixed parameter: Powder layer thickness 67° stripe rotation scanning strategy, high-purity argon protective atmosphere.
[0041] Tensile property test results show that, within the process parameter range of this invention, the tensile strength of all samples is in the range of 900-1034 MPa. Figure 4This indicates that the effects of each process parameter on tensile properties are not significant (response surface model is not significant). Figure 5 This indicates that when the laser power varies within the range of 250-350W, the tensile strength does not show a significant decreasing trend; when the scanning speed varies within the range of 700-1000mm / s, the tensile strength remains stable; and when the scanning spacing varies within the range of 80-100μm, the tensile strength also remains stable.
[0042] In summary, the silicon nitride whisker-reinforced nickel-based alloy composite material of the present invention with high process tolerance can stably obtain excellent mechanical properties within a wide range of SLM process parameters, exhibiting significant high process tolerance characteristics. Its process stability is significantly better than that of the traditional SLM-formed IN718 alloy (the latter usually shows significant performance degradation within 10% deviation of the parameters from the optimal value).
[0043] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance, characterized in that, The composite material consists of a nickel-based alloy matrix and a silicon nitride whisker reinforcing phase, wherein the silicon nitride whiskers are uniformly distributed in the nickel-based alloy matrix; the composite material is dense and crack-free, and has high process tolerance when used for selective laser melting forming.
2. The silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance according to claim 1, characterized in that, When the composite material is used for selective laser melting forming, under the process parameters of laser power 250-350W, scanning speed 700-1000mm / s, and scanning spacing 80-100μm, the tensile strength of the obtained composite material is 900-1034Mpa.
3. The silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance according to claim 1, characterized in that, The silicon nitride whiskers have a length of 10-40 μm, a diameter of 3-5 μm, and an aspect ratio of 2-13.
4. The silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance according to claim 1, characterized in that, The nickel-based alloy matrix is IN718 nickel-based alloy powder, and the particle size of the IN718 nickel-based alloy powder is 15-65μm.
5. The silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance according to claim 1, characterized in that, The amount of silicon nitride whiskers added is 5% of the total mass of the composite material.
6. The method for preparing the silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance according to any one of claims 1-5, characterized in that, Includes the following steps: A nickel-based alloy matrix and silicon nitride whiskers are subjected to acoustic resonance mixing under a protective atmosphere to obtain a silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance.
7. The method for preparing the silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance according to claim 6, characterized in that, When mixing acoustic resonances, the resonance frequency is 50-60Hz, the acceleration is 20-40g, and the mixing time is 3-10min.
8. The method for preparing the silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance according to claim 6 or 7, characterized in that, During acoustic resonance mixing, the resonance frequency was 55Hz, the acceleration was 30g, and the mixing time was 5min.
9. An additive manufacturing method, characterized in that, Includes the following steps: The silicon nitride whisker-reinforced nickel-based alloy composite material with high process tolerance as described in any one of claims 1-5 is formed by selective laser melting; during selective laser melting, the laser power is 250-350W, the scanning speed is 700-1000mm / s, the scanning spacing is 80-100μm, the powder thickness is 40μm, and the scanning strategy is 67° stripe rotation scanning.